Preparation and photocatalytic of g-C3N4/Ta2O5 composite - Nguyen Van Kim; Nguyen Thi Viet Nga; Le Thi Bich Tuyen; Nguyen Tien Trung; Le Truong Giang; Vo Vien (My University, 2015)
Preparation and photocatalytic of g-C3N4/Ta2O5 composite
Keywords: g-C3N4/Ta2O5